2020
DOI: 10.1186/s12957-020-01979-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the risk of permanent stoma after low anterior resection in rectal cancer patients

Abstract: Background: One of the most severe complications of low anterior rectal resection is anastomotic leakage (AL). The creation of a loop ileostomy (LI) reduces the prevalence of AL requiring surgical intervention. However, up to one-third of temporary stomas may never be closed. The first aim of the study was to perform a retrospective assessment of the impact of LI on the risk of permanent stoma (PS) and symptomatic AL. The second aim of the study was to assess preoperative PS risk factors in patients with LI. M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Before ostomy reversal was performed, the anastomotic integrity was confirmed by additional diagnostic modalities such as contrast enema or endoscopy. In line with other studies, a permanent diverting ostomy due to non-reversal was defined as a persistent diverting ostomy at 18 months after creation [18,19]. Delayed reversal was defined as reversal after more than 6 months after creation [20].…”
Section: Treatment and Definitionsmentioning
confidence: 72%
“…Before ostomy reversal was performed, the anastomotic integrity was confirmed by additional diagnostic modalities such as contrast enema or endoscopy. In line with other studies, a permanent diverting ostomy due to non-reversal was defined as a persistent diverting ostomy at 18 months after creation [18,19]. Delayed reversal was defined as reversal after more than 6 months after creation [20].…”
Section: Treatment and Definitionsmentioning
confidence: 72%
“…However, it is important to mention that up to one-third of stomas are never reversed. 10 The question arises whether we are on a good track or not. The decrease of 40% in stoma use coincided with an increase in AL, and like several other studies, our data showed a protective effect of the defunctioning stoma on both the incidence and severity of AL.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with a defunctioning stoma have stoma-related complications (eg, stoma necrosis or stenosis, retraction, parastomal hernia dehydration). 10 In many cases, the prolonged length of stay was likely because of stoma management or so that the problem that initially required the stoma could be further managed. 27 It is likely that patients also had a longer length of stay because of the associated increased likelihood of minor surgical complications and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] During this period, although the distal bowel of the loop stoma is in an open state, there will still be the production of intestinal secretions and partial excrement because of the untimely shunt, which will impact the recovery of bowel function after stoma closure. 6,7 Moreover, postoperative ileus caused by intestinal dysmotility induced by mechanical stimulation of colorectal surgery can aggravate postoperative bowel dysfunction. 8 Anterograde lavage is performed from the distal end of the stoma.…”
mentioning
confidence: 99%